Implementation of Public Sector Accounting in a Government Agency - Masnia; Haliah; Nirwana (Indonesian Journal Publisher, 2024)
Government Agencies are all government institutions with the function of carrying out tasks or functions of government administration in the operational environment, from those at the center to those in the regions, including commissions, agencies and councils that receive funding from the APBN or APBD. The demand for public transparency requires a system to create maximum good performance and accountability to make a government accessible from fraudulent acts detrimental to the state. Public sector accounting is an accounting system used by government institutions or public service institutions as a method or tool for accountability to the general public. This research aims to discover and understand the importance of implementing Public Sector Accounting in a government agency. This research uses a qualitative descriptive method. This research indicates that every government agency must implement public sector accounting because it can simplify and improve the quality of financial reporting.